Investigation on Savonius Wind Turbine in Directed Flow - Mohd Hafiz bin Amran, Mohd Hafiz (Universiti Teknologi PETRONAS, 2008)
The Savonius wind turbine is normally installed in vertical axis configuration and operates in open atmosphere. The wind energy from atmosphere is converted into a mechanical energy rotating of the rotor to produced either electricity or torque. In this study the turbine is to be installed horizontally on top of a chimney. Three different configurations are proposed. The first proposed configuration will exposed the entire rotor to the wind stream. In the second configuration the wind stream will directed to a concave vane by manipulating the angle of flow direction. In the last proposed configuration a guide plate is inserted at one side of the rotor as a casing. An analysis has been conducted on these three different configurations with experimental procedure to verify the result obtained with numerical analysis method in previous work.